Teaching Games for understanding: A learning model that increases student motivation in Physical Education - Sholehudin, Indra; Fendrian, Ferry; Budiman, Ali (Journal of Physical and Outdoor Education, 2025)
Teaching Games for Understanding (TGfU) is a learning model that provides students with game-based knowledge. As research on TGfU continues, attention is focused on student learning motivation. This study contains a literature review related to Teaching Games for Understanding (TGfU) that can increase learning motivation in schools, to support the idea that this model can motivate students in physical education, this study used 10 journals from the data base, namely Google Scholar, Sage journal and Taylor & Francis. With further analysis using synthesis technique. This study aims to pursue Teaching Games for Understanding (TGfU) in student learning motivation in physical education, this study is an updated review of how the application of Teaching Games for Understanding (TGfU) can build student motivation in physical education, including the latest research trends for future research.